Faire naître à la maison en France - Rosanna Sestito (Anthropologie & Santé)
In France, although the majority of deliveries take place in hospitals, some women request to give birth at home with a midwife. However, in recent years, many midwives practicing home births have seen their license revoked by their colleagues in the National Council of Midwives. Based on a sociological survey carried out in France between 2015 and 2016 on the complaints that lead to their exclusion and the prohibition to practice, this article presents their reflections about the technicization of childbirth. The article analyses their discourses, in which the power relationships between them and the medical establishment, the antagonism between different models of perinatal care and feminist and ecologist stances play a central role.